KERAJINAN KAIN TENUN TRADISIONAL DI DESA SUKARARA KABUPATEN LOMBOK TENGAH - Sandi, Septian Ari; Eka Harsana Koriawan, Gede; Suartini, Luh (Universitas Pendidikan Ganesha, 2025)
The purpose of this study is to describe the motifs of woven fabric crafts produced in Sukarara Village. This study uses a qualitative research type with a descriptive approach. The subjects of this study are the owner of the Patuh Cooperative Art Shop gallery and woven fabric artisans in Sukarara Village, Central Lombok Regency. The object of the study is the woven fabric motifs produced in Sukarara Village, Central Lombok Regency. The data collection techniques used include observation, interviews, documentation, and literature review. The data analysis techniques used are domain analysis and taxonomic analysis. The results of the study show: 1) Various motifs of woven fabric crafts produced. The conclusion of the study is that traditional woven fabric crafts in Sukarara Village still have a variety of distinctive motifs.